2014
DOI: 10.1088/0741-3335/56/9/095027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion temperature on modulational instability and envelope solitons of ion acoustic waves in nonthermal electron–positron–ion plasmas

Abstract: The modulational instability and envelope solitons of ion acoustic waves in an unmagnetized nonthermal electron-positron-ion (epi) plasma are investigated. The ions are taken to be dynamic and warm while electrons and positrons are assumed to be inertialess and hot which follow the kappa (or Generalized Lorentzian) distribution. The Krylov-Bogoliubov-Mitropolsky method is used to derive the nonlinear Schrödinger equation for nonlinear amplitude modulation of ion acoustic waves in nonthermal epi plasmas with wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Where β 1 is a constant depending on the parameter q and µ. Here,|q-q c |is the small and dimensionless parameter and can be given as expansion parameter ε i.e.,|q-q c | ≅ ε and s=1 for q >q c and s= -1for q < q c . So, ρ (2) can be expressed as…”
Section: Gardner Equation and Its Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Where β 1 is a constant depending on the parameter q and µ. Here,|q-q c |is the small and dimensionless parameter and can be given as expansion parameter ε i.e.,|q-q c | ≅ ε and s=1 for q >q c and s= -1for q < q c . So, ρ (2) can be expressed as…”
Section: Gardner Equation and Its Solutionmentioning
confidence: 99%
“…Motivated by these events, Cairns et al(1995) showed that the presence of nonthermal electrons changes the nature of the ion sound solitary structures and allows the existence of both positive and negative ion-acoustic (IA) solitary structures, like those observed by Freja and Viking. Various observations of fast ions and electrons in interplanetary space environments clearly indicate that these particles have velocity distribution functions that deviate from the Maxwellian behaviour (Asbridge et al,1968;Divine and Garret, 1983;Krimigis et al, 1983;Lundlin et al, 1989;Futaana et al, 2003;Shan et al, 2014;Akhtar et al, 2014). Therefore, the Maxwellian distribution may be inadequate to describe the long range interactions in plasmas in the presence of nonequilibrium stationary states because the Maxwellian distribution is valid only for the macroscopic ergodic equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by these events, Cairns et al [3] showed that the presence of nonthermal electrons changes the nature of the ion sound solitary structures and allows the existence of both positive and negative ion-acoustic (IA) solitary structures, like those observed by Freja and Viking. Various observations of fast ions and electrons in interplanetary space environments clearly indicate that these particles have velocity distribution functions that deviate from the Maxwellian behavior [4][5][6][7][8][9][10]. Therefore, the Maxwellian distribution may be inadequate to describe the long range interactions in plasmas in the presence of nonequilibrium stationary states because the Maxwellian distribution is valid only for the macroscopic ergodic equilibrium state.…”
Section: Introductionmentioning
confidence: 99%